Evolution of open defecation prevalence in Tanzania 2002–2015: evidence from national demographic and health surveys. Issue 1 (2nd January 2021) - Maliti, Emmanuel
ABSTRACT: Open defecation is one of the health-related development challenges in most developing nations. This study confirms that open defecation prevalence is on the decline in Tanzania and the decline has been pro-poor. Despite such progress, open defecation practices continue to concentrate in the north-eastern and lake zone regions of the country. Education, age, rurality and wealth remain important factors in explaining open defecation. However, the influence of wealth and rurality has evolved over time. Whereas wealth has had an increasing influence over time on whether one defecates in the open, the influence of rurality is on the decline.